Analisis Tingkat Penerimaan Mahasiswa Terhadap Aplikasi Zoom Meeting Sebagai Media Perkuliahan Menggunakan Metode TAM - Muhammad Ifan Rifani Ihsan; Rabiatus Saadah; Rizka Dahlia; Badariatul Lailiah; Hendri Mahmud Nawawi (LPPM Universitas Bina Sarana Informatika, 2022)
The increasingly advanced technology makes it easier for anyone to use it for various activities, such as lecture activities. Especially during the Covid-19 pandemic that has occurred since 2019 until this research was conducted. Covid-19, formerly known as SARS-CoV2, is an outbreak of pneumonia that originates from a virus. This virus was first heard in Wuhan, China in December 2019 (Ciotti et al., 2020). Lectures are conducted online to prevent the spread of this virus. One of the technologies widely used during the Covid-19 pandemic is video conferencing. With video conference meetings can be held even if the people present are far from each other. Zoom is a cloud-based application that is currently often used as a video communication (Azkiya, 2021). Zoom is a video conferencing application that is currently being used in various activities, including lectures. Because it is important to know how much student acceptance of the Zoom application they use for lectures is. The research was conducted using the Technology Acceptance Model or TAM method which consists of three constructs, namely Perceived Usefulness, Perceived Ease of Use and Acceptance of Technology. The data was obtained by distributing questionnaires with a Likert scale of 1 to 5. The data obtained were then calculated using the Structural Equation Model or SEM method consisting of the Outer Model and Inner Model calculations. SEM is an analytical technique that allows testing of a series of simultaneous relationships (Gardenia, 2018). The conclusion is that by taking the R-Square value, the construct in the TAM method is able to measure as much as 63% of student admission case studies on Zoom as a lecture medium. Keywords: Analysis, TAM, Zoom.